A autonomia da Perícia Criminal Oficial no âmbito da Polícia Federal: percepções e reflexões dos profissionais do Sistema de Justiça Criminal - Amorim, José Viana (2012)
This study deals with the issue of the Criminal Forensics’s autonomy in relation to the Brazilian Federal Police. The study, notably of a descriptive nature, with exploratory phases, aims to describe the perceptions and reflections revealed by the thematic analysis of the individuals involved in the issue. For this purpose, the methodology used in the study was content analysis, according to Bardin (1977). The selected individuals were chosen using the criteria of accessibility and type of function: Federal Police Delegado, Criminal Expert of Federal Police, Federal Judge and the District Attorney. In face of its predominately qualitative character, there is no expectation of generalizations of the results obtained in the field, as well as the selection of these individuals did not prioritize quantitative representation. The theoretical reference was constructed with the objective to contextualize and to favor the reader's understanding of how is constituted the reality in which itself insert the object of study, seeking to describe the necessary terms and concepts for this understanding, such as: (i) what is the Criminal Justice System and how its process of formation evolved in the modern State; (ii) what is the structure and flow of the basic procedural of the Brazilian model, highlighting the position in which the Criminalist organs or institutes belong; (iii) what is the level of efficacy of this system in Brazil and what are the main problems that affect the functionality of the Criminal Forensics in its structure; (iv) what are the reactions to the use of paradigms, repressive and preventive, by the State in control of violence, criminality and impunity of criminals, seeking to guarantee the maintenance of public order and social wellbeing; (v) what relevance does the role of the Criminal Forensics have on the Criminal Justice System according to the preventive paradigm; (vi) what is Criminalistics and what is the nature of its activity; (vii) how the current administrative structure and the Criminal Investigation Officer’s network of clients is presented. The researcher then comes to the purpose of the study, describing the process of the Criminalist’s autonomy in Brazil, its origin and how this process came to be designed and focusing on the principal administrative and statutory measures that furthered its consolidation in the country in relation to public security policy, such as: the approval of federal government's plans PNSP (2002), PNDH I (1996), PNDH II (2002) and PNDH III (2009) in addition to the enactment of Law nº 12.030/2009, which specifically assures the scientific-technical and functional autonomy of the Criminal Forensics’s role. Special treatment was given to the significance and reach of the conceptual dimensions of the term 'autonomy' in relation to the Criminal Forensics’s function. To the degree of the weight of the results obtained, the conclusions reveal that the complexity of the theme, theory and practice, awaits the continuity of future research.